2017
DOI: 10.1111/dmcn.13595
|View full text |Cite
|
Sign up to set email alerts
|

Focal cortical malformations in children with early infantile epilepsy and PCDH19 mutations: case report

Abstract: In this case report we assess the occurrence of cortical malformations in children with early infantile epilepsy associated with variants of the gene protocadherin 19 (PCDH19). We describe the clinical course, and electrographic, imaging, genetic, and neuropathological features in a cohort of female children with pharmacoresistant epilepsy. All five children (mean age 10y) had an early onset of epilepsy during infancy and a predominance of fever sensitive seizures occurring in clusters. Cognitive impairment wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
1
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 16 publications
2
50
1
4
Order By: Relevance
“…There were only two cases that had nonspecific abnormalities on cranial MRI. Although some studies found cortical dysplasia in PCDH19 mutation patients and mouse models(Kurian et al, 2018;Pederick et al, 2018), this was not found in our patients. Interictal EEG showed transient focal or multiple epileptiform discharges in only four patients.…”
contrasting
confidence: 94%
See 2 more Smart Citations
“…There were only two cases that had nonspecific abnormalities on cranial MRI. Although some studies found cortical dysplasia in PCDH19 mutation patients and mouse models(Kurian et al, 2018;Pederick et al, 2018), this was not found in our patients. Interictal EEG showed transient focal or multiple epileptiform discharges in only four patients.…”
contrasting
confidence: 94%
“…After discovering that the level of allopregnanolone and steroidogenesis decreased (Tan et al, ; Trivisano et al, ), clinical trials began with ganaxolone, a synthetic analog of isoprogesterone (Tan et al, ). Surgical excision can reduce seizures in patients with cortical dysplasia (Kurian et al, ). Children with PCDH19 ‐GCE had better responsiveness to benzodiazepines in the acute stage, and midazolam could control epileptic seizures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unusual focal temporal-occipital anomalies can be identified in a few patients and raise the possibility of a structural lesion. Interestingly, in the literature, a recent study (Kurian et al, 2018) has reported, for the first time, an association between focal cortical malformations (focal cortical dysplasia and nodular heterotopia) and early-infantile epilepsy and PCDH19 mutation in five female children. Two of these patients underwent surgery with an improvement in seizure control.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies on PCDH19 knock‐out mice (Pederick et al , ) revealed no gross brain morphological defects, suggesting that PCDH19 was dispensable for brain development in species other than zebrafish. However, more recent studies reported the presence of cortical malformations in EIEE9 patients (Kurian et al , ; Pederick et al ., ) reinforcing the idea of PCDH19 involvement in cellular processes that ultimately influence brain morphology, such as neuronal migration.…”
Section: Mutations In Pcdh19 Gene and Encephalopathiesmentioning
confidence: 99%